Does the shadow economy raise observed aggregate efficiency? A cross-country comparison - Pierre-Guillaume Méon; Friedrich G. Schneider; Laurent Weill; Axel Dreher (Johannes Kepler University of Linz, Department of Economics, 2006)
We analyze how adding the shadow economy to official output figures affects technical efficiency. We find that this only slightly affects the ranking of efficiency scores, but increases average efficiency. Our results are robust to the functional form of the production technology and the adjustment of labor to account for years of schooling.
Keywords: O11; O17; O47; O5; 330; shadow economy; income; aggregate productivity; efficiency; Schattenwirtschaft; Technische Effizienz; Produktivität; Vergleich; Welt